PENDIDIKAN AGAMA ISLAM DI ERA GLOBALISASI - Abdul Khobir (Jurnal Forum Tarbiyah, 2009)
Globalization causes the flow is so fast and can not be dammed, and so numerous and diverse flow of information. And the flow of information is not only an effect on knowledge but also to the values of Islamic religious education. So sometimes religious values are being abandoned, because it was considered old-fashioned and out, while those who follow the trend is considered advanced and modern yet started to leave the religious values and morals in life. To counteract the impact of globalization, hence, one of the methods is through education, the religion of Islam.